Elimination of Nickel from Copper Scrap Melt - Hiroyuki Sano; Shin-ya Iwahori; Mitsuru Tanahashi; Toshiharu Fujisawa; Chikabumi Yamauchi (The Minerals, Metals and Materials Society, 2000)
"Pyrometallurgical process using Cu2O-based slag was proposed as a recycling process for copper scrap. However, it is difficult to remove nickel from copper by oxidative refining. Therefore, it is necessary to reduce the concentration of nickel in copper before the oxidative refining. In the present work, the copper enrichment stage in this recycling process, where copper scrap melt is separated into the Fe-C-Cu melt and the molten copper, was taken up and the compositions of both melts were measured. Based on the above results, the distribution ratios of nickel between the Fe-C-Cu melt and the molten copper were calculated. Furthermore, the optimum condition of copper enrichment stage was discussed from the viewpoint of nickel removal and copper recovery. The possibility of recovering 4N-purity copper by using this recycling process was confirmed.IntroductionRecycling is well known as a method for saving resources and reducing environmental damage. More than 99% of copper is used in metallic form - as metal or copper alloys[l]. High-grade copper scrap is directly re-melted and reused, while low-grade copper scrap is transported to copper smelters to be pyrorefined and electrorefined. Nevertheless, a great amount of copper is being stockpiled in the cities and should be recycled in the near future. At that time, the current recycling process will face new problems due to the increases in the recycling rate to the smelters. This includes insufficient combustion heat to melt copper scrap and ·almost no benefit in electrorefining because the scrap does not contain gold and silver. Thus, an alternative pyrometallurgical method for copper scrap refining will be required."